The Ballygiblins: British Emigration Policy, Irish Violence, and Immigrant Reception in Upper Canada - Smith, Laura (Ontario History, 2016)
Drawing on interpretations and reactions to the violence of the 1824 Ballygiblin riot in the Bathurst District of Upper Canada, this article examines the local reception of assisted Irish Catholic immigrants to the region. In their reaction to the new arrivals, Bathurst District residents demonstrated the extent to which local priorities for settlement were at odds with that of British emigration policy. The reception of the Irish was conditioned by the legacy of the so-called “old world” in real and expected patterns of violence; by a local culture that prized loyalty, Protestantism, and pioneer manhood; and by the immediate context of British emigration policy and the process by which that policy was applied, interpreted, and experienced.